(untitled) (Medical Forum Monthly, 2020)
Objective: To compare intravenous dexamethasone with perineural dexamethasone as adjunctive in bupivacaine in ultrasound guided interscelene block. Study Design: Randomized control trial study. Place and Duration of Study: This study was conducted at the Operation theatres of Sahara Medical College from 01-08-2019 to 01-06-2020. Materials and Methods: In randomized control trial 135 patients divided in Group X,Y,Z and received bupivacaine, intravenous Dexamethasone 0.25 mg/kg, perineural dexamethasone 0.15mg/kg as adjunctive in interscelene block. Results: Mean onset of sensory block in minutes was 9.17+1.34, 9.48+1.42 and 8.3+1.01 consecutively in groups X, Y and Z. Time to onset of sensory block was lowest in group Z and highest in group X with significant level of 0.001. Onset of motor block in minutes 10.4+1.03, 10.28+1.19, 9.31+0.96 consecutively in groups X, Y and Z. Time of onset of motor block was significantly low in group Z and highest in group X with significance level of 0.001. Mean time of analgesia in minutes was 820.08+64.01, 901.96+48.01, 972+27.8 consecutively in groups X, Y and Z. Time of analgesia was highest in group Z and was lowest in group X with significance level of 0.001. Conclusion: Higher doses of I/V dexamethasone can prolong analgesia and shorten onset of motor and sensory block when compared with bupivacaine alone but not superior to perineural dexamethasone in conjunction with bupivacaine in interscelene block.